Anthropology and the Bushman - Barnard, Alan (Berg Publishers, 2007)
'The Bushman' is a perennial but changing image. The transformation of that image is important. It symbolizes the perception of Bushman or San society, of the ideas and values of ethnographers who have worked with Bushman peoples, and those of other anthropologists who use this work. Anthropology and the Bushman covers early travellers and settlers, classic nineteenth and twentieth-century ethnographers, North American and Japanese ecological traditions, the approaches of African ethnographers, and recent work on advocacy and social development. It reveals the impact of Bushman studies on anthropology and on the public. The book highlights how Bushman or San ethnography has contributed to anthropological controversy, for example in the debates on the degree of incorporation of San society within the wider political economy, and on the validity of the case for 'indigenous rights' as a special kind of human rights. Examining the changing image of the Bushman, Barnard provides a new contribution to an established anthropology debate.'The Bushman' is a perennial but changing image. It symbolizes the perception of Bushman or San society, of the ideas and values of ethnographers who have worked with Bushman peoples, and those of other anthropologists who use this work. This book reveals the impact of Bushman studies on anthropology and on the public.Alan Barnard is Professor of the Anthropology of Southern Africa at the University of Edinburgh.